Employee perception of CSR activities among CSR-involved institutions in Malaysia / Shahirah Idrus - Idrus, Shahirah (Faculty of Business and Management, 2018)
Corporate Social Responsibility (CSR) has become a focus in organisations as a means to achieve sustainability. Prior studies have found the relation between CSR and other aspects of organisations, namely the financial performance and marketing. This shows that CSR is becoming increasingly relevant in the world today. This paper investigates the employee perception of CSR activities in CSR-involved institutions in Malaysia. Furthermore, it analyses the relationship between perceived fit between corporate culture and CSR activities with employee perception of CSR activities. This research also examines the relationship between perceived CSR capabilities with employee perception of CSR activities. The dependent variable is the employee perception of CSR activities. The first independent variable is perceived fit between corporate culture and CSR activities while the second independent variable is perceived CSR capability. IBM SPSS Statistics V22.0 is used to analyse the relationship between the independent and dependent variables by using multiple regression analysis.